2005
DOI: 10.1128/iai.73.2.1052-1060.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capsulation of Opportunistic Pathogenic Bacteria on Binding of the Pattern Recognition Molecules Mannan-Binding Lectin, L-Ficolin, and H-Ficolin

Abstract: Mannan-binding lectin (MBL), L-ficolin, and H-ficolin are pattern recognition molecules of the innate immune system. We investigated their ability to bind to different serotypes and noncapsulated variants of two gram-positive bacterial species, Streptococcus pneumoniae and Staphylococcus aureus. MBL did not bind to capsulated S. aureus or capsulated S. pneumoniae but did bind to a noncapsulated S. aureus variant (Wood). L-ficolin bound to some capsulated S. aureus serotypes (serotypes 1, 8, 9, 11, and 12) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
161
5
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 44 publications
(43 reference statements)
11
161
5
4
Order By: Relevance
“…This also means that the surfaces of some pathogens can induce the formation of the active conformation of the FBG domains and thereby increase the avidity for the surface. Indeed, the binding specificity for various bacteria differs among ficolins (9,20,22,29,32,45). Such surface-dependent conformational changes would facilitate the discrimination between self and non-self.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also means that the surfaces of some pathogens can induce the formation of the active conformation of the FBG domains and thereby increase the avidity for the surface. Indeed, the binding specificity for various bacteria differs among ficolins (9,20,22,29,32,45). Such surface-dependent conformational changes would facilitate the discrimination between self and non-self.…”
Section: Discussionmentioning
confidence: 99%
“…Since the corresponding residues of the ligandbinding site in H-ficolin differ from those in L-ficolin, Mficolin, and TL5A, its manner of ligand binding may differ. These differences would contribute to the range of pathogen recognition specificity (9,20,22,29,32,45).…”
Section: Discussionmentioning
confidence: 99%
“…The lectin pathway via MBL has both antibody-dependent and antibody-independent modes of activation. H and L ficolins have been shown to bind to a range of bacterial species (Krarup et al, 2005). M-ficolin is a cell-surface protein that has not been widely studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…L-ficolin binds to GlcNAc residue next to galactose at the nonreducing terminal of the oligosaccharide (21). Several reports recently showed that L-ficolin could bind to various acetylated compounds, 1,3-β-D glucan, a molecular marker of yeast and fungal cell walls, lipopolysaccharide (LPS) on gram-negative bacterial species and Lipoteichoic Acid (LTA) on the gram-positive bacteria Staphylococcus aureus and Streplococcus pneumoniae, following the activation of complement (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%